Addition of anaerobic ammonium oxidation bacteria to lower running cost during the membrane bioreactor process treating sewage. (23rd December 2021) - Sun, Ronglin; Zhang, Wenjie
Abstract: Reducing energy consumption or running cost associated with the membrane bioreactor (MBR) process is a serious challenge that needs to be addressed in treating sewage. The addition of anaerobic ammonium oxidation bacteria (AnAOB) to a running MBR has the potential to lower the aeration rate, thus decreasing the running cost in treating sewage. The results obtained showed that owing to addition of AnAOB, TN and NH4 + -N removal rates increased by 9.8% and 1.13%, respectively, while the aeration rate decreased by 50%. Additionally, high throughput sequencing and isotope experiments showed that both AnAOB and heterotrophic denitrification bacteria could survive simultaneously and play an important role in nitrogen removal, with AnAOB having a significantly greater contribution. It can be concluded that the addition of AnAOB reduced the running cost of MBR in treating sewage. HIGHLIGHTS: TN and NH4 + -N removal rates increased by 9.8% and 1.13% with AnAOB addition; AnAOB addition resulted in a decrease in the aeration rate by 50%; Both AnAOB and HDB play an important role in nitrogen removal; AnAOB contributed more significantly to nitrogen removal than HDB. Graphical Abstract